A convenient route for the alkoxylation of biodiesel and its influence on cold flow properties - Mushtaq, M. (2014)
The attachment of alkoxy side chains to biodiesel and the associated effects on its cold flow properties are reported. High oleic methyl ester biodiesel was epoxidized using peroxy formic acid and subsequently alkoxylated using nine different alcohols employing BF3-ethereate complex as catalyst. A low molar excess for alcohols was used at moderately low reaction temperatures (40-50°C). A high conversion for attachment of alkoxy group ranging 84-93 was achieved with excellent selectivity. Cloud points, pour points, and kinematic viscosities were measured to evaluate the cold flow properties of modified biodiesel. The lowest cloud point -11°C and pour point -14°C were obtained with n-decoxy biodiesel. Elevated kinematic viscosities were observed for all alkoxylated products. The lowest kinematic viscosity (6.26 mm2·s-1) was observed for methoxy biodiesel. Gas chromatography mass spectrometry (GC-MS), proton nuclear magnetic resonance (1H NMR), 13C NMR, and Fourier transform infrared (FT-IR) were used for structural elucidation. The reported alkoxylation route has high conversion rate and is convenient to implement. © 2014 Taylor and Francis Group, LLC.